Laterality judgement and tactile acuity in patients with frozen shoulder: A cross-sectional study. (June 2020) - Mena-del Horno, S.; Balasch-Bernat, M.; Dueñas, L.; Reis, F.; Louw, A.; Lluch, E.
Abstract: Background: Disrupted tactile acuity and poor laterality judgement have been shown in several chronic musculoskeletal pain conditions. Whether they are impaired in people with frozen shoulder (FS) remains unknown. Objectives: To determine whether there is impairment in tactile acuity and laterality judgement in subjects with FS. Methods: Thirty-eight subjects with idiopathic FS and 38 sex and age-matched healthy controls were enrolled. The two-point discrimination threshold (TPDT) over the affected and unaffected shoulder of patients with FS and shoulder of healthy controls was evaluated. In addition, all participants performed a left/right judgment task (LRJT). Independent and dependent t-tests were used to compare group means. Pearson-product moment coefficient correlations between pain intensity and duration and LRJT and TPDT were calculated for the FS group. Results: The TPDT over the affected shoulder was significantly increased compared to the unaffected shoulder (mean difference, 3.82 mm; 95% confidence interval [CI]:0.53, 7.10; p = .02) and controls (mean difference, 5.80 mm; 95% CI: 1.09, 10.52; p = .02). Patients with FS were less accurate (mean difference, 5.90%; 95% CI: 0.36, 11.43; p = .03) and slower (mean difference, −0.26 s; 95% CI: 0.06, 0.45; p = .01) responding to images of their affected shoulder compared to their unaffected shoulder. No associations were found between pain intensity and duration and either TPDT or laterality judgement. Conclusions: Participants with FS demonstrated reduced tactile acuity and impaired laterality judgement over their affected shoulder compared to their unaffected shoulder. When compared to controls, subjects with FS showed reduced tactile acuity. Trial registration ClinicalTrials.gov Identifier: NCT03320200 . Highlights: Tactile acuity is reduced in subjects with FS over the affected shoulder. Subject with FS have reduced tactile acuity compared to healthy controls. Individuals with FS are less accurate and slower in a LRJT in the affected shoulder. Further research is needed to unravel the role of central pain mechanisms in FS.